Analisis kelayakan finansial usaha beras aruk pada masa pandemi covid-19 (studi kasus: kelompok tani Sumber Jaya Desa Tempilang Kabupaten Bangka Barat) - Eni Karsiningsih (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Introduction: During the Covid-19 pandemic, aruk rice became one of the healthy alternative food additives for consumption. Aruk rice is a local food of cultural heritage for the people of Bangka Belitung that must be preserved. This study aims to analyze the financial feasibility of the aruk rice business during the Covid-19 pandemic carried out by the Sumber Jaya Farmers Group, Tempilang Village, West Bangka Regency. Method: The research method used is a case study. Sampling was carried out by census, which took 8 aruk rice makers who produced during the Covid-19 pandemic. Analysis of the financial feasibility of aruk rice business is carried out by calculating NPV, Net B/C ratio, IRR, Payback Period, and BEP. Result: The results showed that during the Covid-19 pandemic, the aruk rice business provided a 12% higher profit, which was Rp. 866,700 per month compared to before the Covid-19 pandemic. Based on the financial feasibility analysis, the aruk rice business during the Covid-19 pandemic is still feasible. Based on the results of the financial feasibility analysis at the interest rate of the BRI Micro KUR loan at 6% per year, the NPV value is Rp. 10,400,400, Net B/C ratio is 1.5, IRR is 128%, and the Payback Period or payback period. investment for 4 months 5 days. The aruk rice business will experience a Break Event Point when the income is IDR 218,200 per month, the production is 9 kg per month and the price is IDR 16,200 per kilo. Conclusion: Based on the results of the financial feasibility analysis, the rice aruk business conducted by the Sumber Jaya Farmers Group during the Covid-19 pandemic is still feasible.